Safety and structural integrity 2006 - Kim, Young-Jin, 1950- (Diffusion and defect data. Solid state phenomena ;, 2007)
The primary objective of this collection of 42 peer-reviewed authoritative articles is to share with the reader the very latest information on cutting-edge technologies in the fields of safety and structural integrity. The topics addressed by this collection span a wide range of issues: including fracture and fatigue cracking, reliability evaluation, NDE, modeling and design. Particular attention is paid to emerging techniques for the treatment of complicated structures.